Overview of the synergistic use of radiotherapy and immunotherapy in cancer treatment: current challenges and scopes of improvement. Issue 2 (1st February 2023) - Colciago, Riccardo Ray; Fischetti, Irene; Giandini, Carlotta; La Rocca, Eliana; Rancati T., Tiziana; Rejas Mateo, Alicia; Colombo, Mario Paolo; Lozza, Laura; Chiodoni, Claudia; Jachetti, Elena; De Santis, Maria Carmen
ABSTRACT: Introduction: Oncological treatments are changing rapidly due to the advent of several targeted anticancer drugs and regimens. The primary new area of research in oncological medicine is the implementation of a combination of novel therapies and standard care. In this scenario, radioimmunotherapy is one of the most promising fields, as proven by the exponential growth of publications in this context during the last decade. Areas covered: This review provides an overview of the synergistic use of radiotherapy and immunotherapy and addresses questions like the importance of this subject, aspects clinicians look for in patients to administer this combined therapy, individuals who would benefit the most from this treatment, how to achieve abscopal effect and when does radio-immunotherapy become standard clinical practice. Expert opinion: Answers to these queries generate further issues that need to be addressed and solved. The abscopal and bystander effects are not utopia, rather physiological phenomena that occur in our bodies. Nevertheless, substantial evidence regarding the combination of radioimmunotherapy is lacking. In conclusion, joining forces and finding answers to all these open questions is of paramount importance.